2000
DOI: 10.1002/(sici)1097-0134(20000301)38:4<414::aid-prot7>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo-minimized energy profile of estradiol in the ligand-binding tunnel of 17?-hydroxysteroid dehydrogenase: Atomic mechanisms of steroid recognition

Abstract: 17 beta-Estradiol (E2) is a potent stimulator of certain forms of breast cancer. The final step of E2 biosynthesis is catalyzed by the estrogenic 17 beta-hydroxysteroid dehydrogenase (17 beta-HSD1), which is an important target for anti-cancer drugs. X-ray crystallography indicated that the binding site for the steroids has a tunnel-like shape. We have used a Monte Carlo-Minimization (MCM) protocol to explore possibilities of interactions of E2 with the binding site tunnel of 17 beta-HSD1. The enzyme was repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 41 publications
2
15
0
Order By: Relevance
“…The active site extends to a proper size to accommodate the substrate when a steroid approaches the site. This is in agreement with the recent results in the study of other steroid-converting enzymes, such as the significant active site volume modification in binding different steroids found in the type 5 human 17␤-hydroxysteroid dehydrogenase (HSD), 2 and the conformational rearrangements found when estradiol advances in the binding site of human estrogenic 17␤-HSD (31).…”
Section: Resultssupporting
confidence: 92%
“…The active site extends to a proper size to accommodate the substrate when a steroid approaches the site. This is in agreement with the recent results in the study of other steroid-converting enzymes, such as the significant active site volume modification in binding different steroids found in the type 5 human 17␤-hydroxysteroid dehydrogenase (HSD), 2 and the conformational rearrangements found when estradiol advances in the binding site of human estrogenic 17␤-HSD (31).…”
Section: Resultssupporting
confidence: 92%
“…These mechanisms of selectivity over C19 steroids, steric hindrance at the A-ring and hydrogen bonding of the hydroxyl groups at either end of the molecule, are also seen in the binding of E 2 to ERa . Modelling has also confirmed that cofactor and substrate may bind in either order (Zhorov & Lin 2000), as was seen in early kinetic activity studies (Betz 1971).…”
Section: Inhibitors Of 17b-hsd1supporting
confidence: 60%
“…In addition to the energy components described in Ref. 33, the energy expression included hydration energy calculated by the method of Lazaridis and Karplus (34) and energy of deformation of bond angles in testosterone. The enzyme was represented by a two-shell model based on our crystallographic structure.…”
Section: Methodsmentioning
confidence: 99%
“…The MCM energy profile was computed with the help of the ZMM program described in Ref. 33 and references therein.…”
Section: Methodsmentioning
confidence: 99%